2001
DOI: 10.1192/bjp.179.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and psychotic symptoms in bipolar affective disorder

Abstract: A link between smoking and psychosis exists in bipolar affective disorder and may be independent of categorical diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 17 publications
3
45
0
Order By: Relevance
“…Our findings support the strong relationship between cigarette smoking and unipolar major depressive disorder [1,2], bipolar disorder [3 Á/6], schizophrenia [1,7,8] and schizoaffective disorder [9], demonstrating that this association is present not only in the United States [1,2,7], Spain [3], Scotland [8], Ireland [5] and Israel [4], but also in Hungary.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings support the strong relationship between cigarette smoking and unipolar major depressive disorder [1,2], bipolar disorder [3 Á/6], schizophrenia [1,7,8] and schizoaffective disorder [9], demonstrating that this association is present not only in the United States [1,2,7], Spain [3], Scotland [8], Ireland [5] and Israel [4], but also in Hungary.…”
Section: Discussionsupporting
confidence: 85%
“…The finding of smoking was interesting. It is consistent with some earlier studies, two with a smaller sample (31,32), and one with a larger sample (33). Smoking seems to be more prevalent in bipolar patients than in normal population, and smoking starts before the onset of the illness (31).…”
Section: General Discussion Of the Resultssupporting
confidence: 91%
“…Smoking seems to be more prevalent in bipolar patients than in normal population, and smoking starts before the onset of the illness (31). Smoking seems to be a predictor for a psychosis (32), and a predictor for a suicidal attempt (33). Smoking has a high heritability estimate, but this regards continuation of smoking, as starting to smoke is psychosocial in origin (34).…”
Section: General Discussion Of the Resultsmentioning
confidence: 96%
“…Goldstein et al (2008) also found positive relationships between smoking status and the severity of depressive episodes and higher rates of comorbid substance use disorder in a sample of adolescents with bipolar disorder (Goldstein et al, 2008). Some studies suggest that smokers with bipolar disorder are more vulnerable to psychotic episodes than non-smokers, but other studies failed to confirm this association (Waxmonsky et al, 2005;Corvin et al, 2001;Cassidy et al, 2002;Heffner et al, 2008). Not all investigations found similar results to the above; for example Heffner et al (2008) found no association between smoking status and the severity and characteristics of bipolar disorder (i.e.…”
Section: Smoking-related Changes In Clinical Characteristics Of Bipolmentioning
confidence: 85%